Emotional Experiences of Mothers Living With HIV and the Quest for Emotional Recovery: A Qualitative Study in Lima, Peru. (July 2019) - Contreras, Carmen; Rumaldo, Nancy; Lindeborg, Michael Masao; Mendoza, Milagros; Chen, David Roy; Saldaña, Olga; Wong, Milagros; Muñoz, Maribel; Schrier, Elizabeth; Lecca, Leonid; Castro, Arachu; Shin, Sonya; et al.
Abstract: Little evidence exists about the emotional experiences of mothers with HIV, and a better understanding is essential to support their emotional health and treatment adherence. We describe the emotional experiences of eight mothers who initiated antiretroviral therapy during pregnancy or within a few years of childbirth in Lima, Peru. An interpretive phenomenological approach was used, and the following themes emerged: (a) emotions involved in diagnosis and disclosure, (b) the meaning of motherhood with HIV, (c) the mothers' roles in seeking and maintaining relationships with partners and families, and (d) mechanisms for resilience and emotional recovery. Participants experienced sadness and denial after diagnosis, which gave way to emotional recovery. Participant abilities to find refuge in caring for children and coordinating support from loved ones proved to be essential. Participants recognized that intense emotions motivated them to seek creative solutions and cited personal growth as an important outcome.